Non-surgical acute cholecystitis: 2 cases of gallbladder rupture after internal endoscopic or percutaneous diversion - Lorenzo Monfardini; Claudio Sallemi; Nicolo' Gennaro; Claudio Bna (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Gallbladder rupture is a rare but serious complication of acute cholecystitis. We describe two cases of acute cholecystitis in patients not candidate for surgery that underwent internal biliary drainage with endoscopic and percutaneous approach, respectively. Both experienced gallbladder rupture  in the postoperative period. The complication occurred after percutaneous internal drainage was treated conservatively, whereas the latter occurred after the endoscopic maneuver required an external percutaneous approach. After a brief revision of the literature about the interventional management of acute cholecystitis, the Authors discuss the possible reasons of galbladder rupture.